Social representations of oncologic surgery for patients with cancer - Rômulo Frutuoso Antunes; Rachel Verdan Dib; Raquel de Souza Ramos; Antonio Marcos Tosoli Gomes; Manassés Moura dos Santos; Margarida Maria Rocha Bernardes; Carolina Cristina Scrivano dos Santos; Karen Paula Damasceno dos Santos Souza (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to analyze the social representations of patients with cancer regarding oncologic surgery. Methods: a qualitative study based on Social Representation Theory was conducted with 126 participants between October 2021 and May 2022 in a public hospital in Rio de Janeiro. A characterization questionnaire, free evocations of the inducing term “surgery”, and semi-structured interviews with 60 participants were applied. Data were analyzed using Microsoft Excel® and IRaMuTeQ. Results: the central core of the representation is composed of fear, cure, hope, and removing the disease. The analysis of interviews resulted in six classes that highlight the social changes caused by treatment as well as the need for a support network to cope with the surgical process. Final Considerations: the representations reflect fear and hope towards the procedure and the desire to remove the disease, thus translating the cure through surgery.